Investigation of encapsulated water wire within self-assembled hydrophilic nanochannels, in a modified γ4-amino acid crystals: Tracking thermally induced changes of intermolecular interactions within a crystalline hydrate - Krishnayan Basuroy; Jose de Jesus Velazquez-Garcia; Simone Techert (Amino Acids)
Abstract Nanostructures formed by the self-assembly of modified/unmodified amino acids have the potential to be useful in several biological/nonbiological applications. In that regard, the greater conformational space provided by γ-amino acids, owing to their additional backbone torsional degrees of freedom and enhanced proteolytic stability, compared to their α-counterparts, should be explored. Though, modified single amino acid-based nanomaterials such as nanobelts or hydrogels are developed by utilizing the monosubstituted γ-amino acids derived from the backbone homologation of phenylalanine (Phe). Examples of a single γ-amino acid-based porous nanostructure capable of accommodating solvent molecules are not really known. The crystal structures of a modified γ4(R)Phe residue, Boc-γ4(R)Phe-OH, at different temperatures, showed that hydrogen-bonded water molecules are forming a wire inside hydrophilic nanochannels. The dynamics of intermolecular interactions between the water wire and the inner wall of the channel with relation to the temperature change was investigated by analyzing the natural bonding orbital (NBO) calculation results performed with the single crystal structures obtained at different temperature points. The NBO results showed that from 325 K onward, the strength of water–water interactions in the water wire are getting weaker, whereas, for the water–inner wall interactions, it getting stronger, suggesting a favorable change in the orientation of water molecules with temperatures, for the latter.